2020
DOI: 10.3390/plants9050560
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Mechanism Involved in Cold Stress Tolerance in Plants

Abstract: Previous studies have reported that low temperature (LT) constrains plant growth and restricts productivity in temperate regions. However, the underlying mechanisms are complex and not well understood. Over the past ten years, research on the process of adaptation and tolerance of plants during cold stress has been carried out. In molecular terms, researchers prioritize research into the field of the ICE-CBF-COR signaling pathway which is believed to be the important key to the cold acclimation process. Induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
173
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(210 citation statements)
references
References 94 publications
3
173
0
2
Order By: Relevance
“…Phytohormones mainly include IAA, GA, CK, ABA, ET, BR, SA, JA, and strigolactone, which are small endogenous signaling molecules. Among them, BR, ABA, IAA, ET, GA, and JA have been reported to respond to cold stress and regulate cold resistance [59][60][61]. Previous studies have demonstrated that JA positively regulated plant cold tolerance [62].…”
Section: Genes Related To Phytohormone Signal Transduction Involved Imentioning
confidence: 99%
“…Phytohormones mainly include IAA, GA, CK, ABA, ET, BR, SA, JA, and strigolactone, which are small endogenous signaling molecules. Among them, BR, ABA, IAA, ET, GA, and JA have been reported to respond to cold stress and regulate cold resistance [59][60][61]. Previous studies have demonstrated that JA positively regulated plant cold tolerance [62].…”
Section: Genes Related To Phytohormone Signal Transduction Involved Imentioning
confidence: 99%
“…The results show that the 90 BpPODs were distributed among 14 chromosomes, as shown in Figure 4, the physical locations of these BpPODs on chromosomes were scattered and uneven. Chromosome 1 and 8 contains the most BpPODs (14), followed by chromosome 13 (10). Eight BpPODs were simultaneously distributed on chromosomes 5 and 7, whereas chromosomes 14 had only one and chromosomes 11 does not include the POD gene.…”
Section: Chromosomal Location and Evolution Analysis Of Bppodsmentioning
confidence: 99%
“…The membrane and temperature sensor (COLD1/RGA1) receives the cold signal, leading to an in ux of Ca 2+ , ROS production, abscisic acid accumulation, and mitogen-activated protein kinase (MAPK) cascade (OsMKK6-OsMPK3) reactions [21,30,31]. ICE-CBF-COR is one of the most widely reported pathways [32]. CBF orthologs have been isolated in rice [21].…”
Section: Introductionmentioning
confidence: 99%